Pengaruh Penjualan Langsung Terhadap Peningkatan Volume Penjualan Paving Blok Pada PT. Baruna Alam Lestari Bandung - Ooy Siti Halimah (Program Studi Manajemen, Universitas Al Ghifari, 2020)
Along with the rapid growth of the economy today, marketing has an increasingly important position in the business world. This is because the purpose of the company to grab market share from the sale of products optimally, quickly is to do direct sales.One form of the use of marketing in the business world, especially in the field of sales is to use direct sales it has the ability to provide information needed by the company and employees.With the effect of face-to-face sales in increasing sales volume paving blocks are designed to meet the needs of such administration, knowing the amount of production of goods every day, managing employee wages and production costs in order to test the relationship between the independent variables with the dependent variable.Based on the hypothesis by using the test